Pelagomanes morawanensis, n. comb. - Trubovitz, Sarah; Renaudie, Johan; Lazarus, David; Noble, Paula (Zenodo, 2022)
Pelagomanes morawanensis (Funakawa, 1995b) n. comb. Plate 40, Figs. 4A – 6, 9, 11–12. Ceratocyrtis morawanensis n. sp., Funakawa, 1995b, pl. 1, figs. 4–5. Ceratocyrtis? morawanensis Funakawa, Renaudie, 2014, pl. 22, fig. 2. Lophophaena tekopua O’Connor, Kamikuri, 2019, pl. 14, fig. 13 (non fig. 14). Lophophaena tekopua O’Connor, Trubovitz et al. , 2020, supplementary data 7. Remarks. Funakawa (1995b) gives no differential diagnosis between this species and Pelagomanes cantharoides (Sugiyama and Furutani, 1992), pl. 40, figs. 1–3, 7–8, 10, 14. The main difference we understand from the written descriptions of these species is the presence of a forked apical horn in P. cantharoides but not in P. morawanensis . As mentioned above, this character alone may not justify separate species. Until a more focused study can be done on these taxa, we retain the separate species concepts with some doubts. Funakawa (1995b) notes that this species is different from P. thaumasia (Caulet) (Pl. 39, Figs. 10A –11) in having longer apical and ventral horns, as well as being large overall. We would add that P. thaumasia tends to have more poorly developed ribs on the thorax than P. morawanensis . Range. Middle Miocene in the EEP (Table 1). One broken specimen was observed in the Pliocene, but it is unclear whether this individual was reworked. Funakawa (1995) described this species from Upper Oligocene material in Japan. Renaudie (2014) reported this species from the Middle Miocene of the Southern Ocean. Published as part of Trubovitz, Sarah, Renaudie, Johan, Lazarus, David & Noble, Paula, 2022, Late Neogene Lophophaenidae (Nassellaria, Radiolaria) from the eastern equatorial Pacific, pp. 1-158 in Zootaxa 5160 (1) on page 81, DOI:10.11646/zootaxa.5160.1.1, http://zenodo.org/record/10544058